First two MRI guided stereotactic body radiation therapy of recurrent sustained ventricular tachycardia. (25th November 2020) - Kovacs, B; Mayinger, M; Tanadini-Lang, S; Ehrbar, S; Wilke, L; Chamberlain, M; Duru, F; Steffel, J; Garcia Schueler, H.I; Manka, R; Ruschitzka, F; Guckenberger, M; et al.
Abstract: Background: Stereotactic body radiation therapy (SBRT) is emerging as a bail-out treatment in patients suffering from therapy resistant ventricular tachyarrhythmias (VT). Purpose: We report the worldwide first cases of real-time magnetic resonance image guided SBRT (MR-SBRT) in recurrent sustained VT and electrical storm (ES) due to dilated cardiomyopathy (DCM). Methods: The patients were male, 71- (patient A) and 74-year-old (patients B) suffering from recurrent VT and ES with ICD shocks, despite guideline-directed medical therapy including maximal antiarrhythmic therapy. Patient A had two endocardial radiofrequency catheter ablation (RFA) and one epicardial surgical RFA and patient B had one endocardial RFA prior. An interdisciplinary decision was made to perform MR-SBRT in palliative intent to minimize repetitive ICD shocks. Results: Areas of VT-substrate were identified to build a volumetric target using the performed EP studies as well as cardiac MRI and CT. A single fraction of 25Gy at isodose 80% was delivered to a planned target volume of 115.1ml and 73ml in the anterior/anteroseptal basal regions in patients A and B, respectively on a dedicated MR linac using real-time MRI tracking. Patient A developed a prolonged ES interpreted as acute radiation-induced inflammation following the treatment, which ceased two days after administration of high-dose dexamethasone. Patient B had no immediate adverse effects from the treatment. Left-ventricular ejection fraction remained stable in both patients at 25%. Both patients had significant improvement of their quality of life. Patient A died 222 days after MR-SBRT due to recurrent ES at another hospital. Patient B is free from VT over six months after treatment. Conclusion: In these first two cases, we demonstrate feasibility, safety and short-term efficacy of MR-SBRT. Funding Acknowledgement: Type of funding source: None